2020
DOI: 10.1172/jci.insight.135952
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the calcium release channel deficiency syndrome

Abstract: are involved in an equity/royalty relationship (no patent numbers involved) with AliveCor, Blue Ox Healthcare Partners, and StemoniX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In addition, RyR2 mutations have also been implicated in non-stress-induced cardiac disease including long QT syndrome [ 57 , 58 ], torsade de pointes [ 59 , 60 ], left ventricular noncompaction [ 61 , 62 ], dilated cardiomyopathy [ 63 , 64 ], and hypertrophic cardiomyopathy [ 65 ]. Very recently, a new disease termed RyR2 Ca 2+ release deficiency syndrome (CRDS) was described, underlined by RyR2 loss of function (LoF) mutations [ 66 , 67 ]. CRDS is characterized by ventricular arrhythmias and sudden cardiac death but a negative exercise stress testing for CPVT.…”
Section: Cardiac Disease Associated With Ryr2 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, RyR2 mutations have also been implicated in non-stress-induced cardiac disease including long QT syndrome [ 57 , 58 ], torsade de pointes [ 59 , 60 ], left ventricular noncompaction [ 61 , 62 ], dilated cardiomyopathy [ 63 , 64 ], and hypertrophic cardiomyopathy [ 65 ]. Very recently, a new disease termed RyR2 Ca 2+ release deficiency syndrome (CRDS) was described, underlined by RyR2 loss of function (LoF) mutations [ 66 , 67 ]. CRDS is characterized by ventricular arrhythmias and sudden cardiac death but a negative exercise stress testing for CPVT.…”
Section: Cardiac Disease Associated With Ryr2 Mutationsmentioning
confidence: 99%
“…In terms of disease diagnosis, there is no apparent correlation between the location of mutations on the RyR2 structure and the clinical phenotype presenting as typical or atypical CPVT. On the other hand, the few deletions, insertions, and nonsense mutations reported to date are often associated with atypical CPVT or cardiomyopathy irrespective of their location on the RyR2 structure (e.g., [ 61 , 63 , 67 , 69 ]).…”
Section: Molecular Mechanisms Of Genetic Ryr2 Diseasementioning
confidence: 99%
“…It is logical to infer that flecainide might exacerbate the CRDS phenotype if it can inhibit RyR2. To date, flecainide has proven to be a promising therapeutic agent for CRDS ( Tester et al, 2020 ; Ormerod et al, 2021 ). The programmed electrical stimulation protocol with a pattern of long-burst, long-pause, and short-coupled (LBLPS) can induce ventricular arrhythmias in transgenic mice with RyR2 LOF mutations.…”
Section: Flecainide Treatment In Calcium-release Deficiency Syndromementioning
confidence: 99%
“… Sun et al (2021) demonstrated that treatment with flecainide abolished LBLPS-induced ventricular arrhythmias in model mice. In the induced pluripotent stem cell cardiomyocytes carrying homozygous RYR2 duplication, which presented LOF, Tester et al (2020) reported that flecainide significantly reduced arrhythmic activity caused by isopropanol. Ormerod et al (2021) tested flecainide in nine CRDS patients and found that the administration of flecainide substantially reduced arrhythmia inducibility in one subject and abolished arrhythmia in all others.…”
Section: Flecainide Treatment In Calcium-release Deficiency Syndromementioning
confidence: 99%
“…During cardiac excitation–contraction coupling, a minor amount of extracellular Ca 2+ enters the cytoplasm through L-type voltage gated calcium channels, triggering the release of large amounts of Ca 2+ into the cytoplasm through RyR2 channels and causing cardiomyocyte contraction. Upon completion of the cardiomyocyte contraction, most of the cytoplasmic Ca 2+ is reabsorbed into ER via SERCA2 ( Tester et al, 2020 ). Apart from the RyR2 protein level, the function of RyR2 is also regulated by its phosphorylation at Ser 2,808 ( Baine et al, 2020 ; Potenza et al, 2020 ).…”
Section: Biological Functions Of Mercsmentioning
confidence: 99%